Diagnosis of aggressive subtypes of eyelid basal cell carcinoma by 2-mm punch biopsy: prospective and comparative study - LUIZ ANGELO ROSSATO; Rachel Camargo Carneiro; Erick Marcet Santiago de Macedo; Patrícia Picciarelli de Lima; Ahlys Ayumi Miyazaki; Suzana Matayoshi (Revista do Colégio Brasileiro de Cirurgiões)
ABSTRACT Objective : to compare the accuracy of preoperative 2-mm punch biopsy at one site and at two sites in the diagnosis of aggressive subtypes of eyelid basal cell carcinoma (BCC). Methods : we randomly assigned patients to Group 1 (biopsy at one site) and Group 2 (biopsy at two sites). We compared the biopsy results to the gold standard (pathology of the surgical specimen). We calculated the sensitivity, specificity, positive predictive value, negative predictive value, accuracy and Kappa coefficient to determine the level of agreement in both groups. Results : we analyzed 105 lesions (Group 1: n = 44; Group 2: n = 61). The agreement was 54.5% in Group 1 and 73.8% in Group 2 (p = 0.041). There was no significant difference between the groups regarding the distribution of quantitative and qualitative variables (gender, age, disease duration, tumor larger diameter, area and commitment of margins). Biopsy at two sites was two times more likely to agree with the gold standard than the biopsy of a single site. Conclusions : the accuracy and the performance indicators were better for 2-mm punch biopsy in two sites than in one site for the diagnosis of aggressive subtypes of eyelid BCC.